Íbúð kanans, lífið á vellinum - Dagný Gísladóttir 1969- (2013)
Eftirfarandi greinargerð er hluti af lokaverkefni höfundar í hagnýtri menningarmiðlun við Háskóla Íslands. Miðlunarleiðin sem varð fyrir valinu er sýning er byggir á upplifun og hvetur til samtals um þá sögu sem 50 ára vera varnarliðs á Íslandi skóp. Titill sýningarinnar er Íbúð kanans, lífið á vellinum og er hún sett upp í íbúð 607 við Vesturbraut eða West Avenue á Ásbrú. Life on a NATO Base is an exhibition that focuses on the everyday lives of U.S. soldiers and their families during their tour of duty at Naval Air Station Keflavik (NASKEF), Iceland. For over half a century, more than 200,000 U.S. citizens lived and worked at NASKEF along with thousands of Icelandic employees That is a high number considering that the Icelandic population is barely more than 300,000. The gates to NASKEF were closed in September 2006, marking the end of an era. The exhibition is a beginning of a conversation that looks at different cultures and how they coexisted during this time. This is a Please Touch exhibition. Share your story and memories with us and help us write history.